Inovasi pendidikan teknik di SMK As-Shofwah NWDI Renco melalui pelatihan robot - Akbar, Taufik; Sandi, Arnila; Satriadi, Ari; Ahmad, Ramli; Ahmadi, Ahwan; Putra, Hadian Mandala; Nuzuluddin, M.; Putri, Intan Komala Dewi; Alfathani, Ahmad Soni; Alimudin, Alimudin (Universitas Hamzanwadi, 2024)
Innovation in technical education plays a crucial role in preparing students to face the challenges of the Fourth Industrial Revolution, especially with the growing demand for skilled workers in automation technology. This article explores the implementation of robotics training at SMK As-Shofwah NWDI Renco as an innovative approach to technical education. The training employed a project-based learning (PBL) method, involving 18 students from grades X, XI, and XII, with 28% of participants from grade X, 33% from grade XI, and 39% from grade XII. Results revealed that the training significantly enhanced students' technical skills in basic robotics, microcontroller usage, sensors, actuators, and robot programming. Additionally, it fostered improvements in learning motivation, critical thinking, and teamwork. Despite its successes, the program faced challenges, including limited resources and the need for further teacher training. This robotics training serves as a strategic step in preparing vocational school students to compete in a technology-driven workforce